Keeping in touch with context: non-verbal behavior as a manifestation of communality and dominance - Sekerdej, M. (2018)
This research investigated the influence of observed touch on the perceptions of communality and dominance in dyadic interactions. We manipulated four key situational features of haptic behavior in two experiments: the initiation, reciprocity, the degree of formality of touch (Studies 1 and 2), and the context of the interaction (Study 2). The results showed that the default perception of touch, irrespective of whether it is initiated or reciprocated, is the communal intention of the toucher. Furthermore, the initiation of touch was seen as an act of dominance, particularly, when the contact between the actors was primed as being hierarchical. Reciprocation neutralized the perceived asymmetry in dominance, but such inferences seemed to hinge on the fit of the touch with the context: reciprocation of formal touch reduced the asymmetry in the hierarchical context, whereas reciprocation of informal touch reduced the asymmetry in the non-hierarchical context.